2010
DOI: 10.1212/wnl.0b013e318200d80c
|View full text |Cite
|
Sign up to set email alerts
|

Absence of cortical demyelination in neuromyelitis optica

Abstract: Objective: To asses the presence of cortical demyelination in brains of patients with neuromyelitis optica (NMO). NMO is an autoimmune inflammatory demyelinating disease that specifically targets aquaporin-4-rich regions of the CNS. Since aquaporin-4 is highly expressed in normal cortex, we anticipated that cortical demyelination may occur in NMO.Methods: This is a cross-sectional neuropathologic study performed on archival forebrain and cerebellar tissue sections from 19 autopsied patients with a clinically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
98
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 27 publications
17
98
4
Order By: Relevance
“…Accordingly, we inferred that atrophy might emerge in olfactory-related cerebral regions, accompanied by other cerebral regions, thereby contributing to olfactory dysfunction. Filippi et al [29] pointed that retrograde degeneration of neurons secondary to spinal cord and optic nerve lesions or GM lesions might be the reasons of normal-appearing GM damage in patients with NMO, and though no pathological findings supported cortical demyelination in NMOSD [4], Saji et al [30] concluded that the pathological process of cortical neurodegeneration contributed to cognitive impairment in NMOSDs, in line with the present imaging results. Brain Values are mean (SD) unless otherwise indicated.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Accordingly, we inferred that atrophy might emerge in olfactory-related cerebral regions, accompanied by other cerebral regions, thereby contributing to olfactory dysfunction. Filippi et al [29] pointed that retrograde degeneration of neurons secondary to spinal cord and optic nerve lesions or GM lesions might be the reasons of normal-appearing GM damage in patients with NMO, and though no pathological findings supported cortical demyelination in NMOSD [4], Saji et al [30] concluded that the pathological process of cortical neurodegeneration contributed to cognitive impairment in NMOSDs, in line with the present imaging results. Brain Values are mean (SD) unless otherwise indicated.…”
Section: Discussionsupporting
confidence: 73%
“…Lesions present as a mirrored distribution of AQP-4, particularly adjacent to the ventricles [3]. Unlike in multiple sclerosis (MS), cortical lesions have not yet been detected in pathological and 7-T magnetic resonance imaging (MRI) studies on NMOSDs [4,5]. The characteristics of these lesions are distinctive in MS, which typically involves periventricular, juxtacortical, and infratentorial regions [6].…”
Section: Introductionmentioning
confidence: 99%
“…This assertion is consistent with the findings of a pathologic study that failed to detect cortical changes that reflected axonal degeneration in patients with NMO. 32 Consequently, the primary neurodegenerative processes (neuronal loss) may at least partially account for the GMV reductions in patients with NMO. This hypothesis is confirmed by the results of a pathologic study that revealed a substantial cortical neuronal loss in NMO spectrum disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive dysfunction is found in approximately 30 % of pediatric MS children and adolescents [33]. In accordance with Popescu et al [24], it can be proposed that cortical demyelination only appears in MS, instead of NMO, and cognitive changes are correlated to cortical atrophy in MS, but not in NMO [34]. An EAE model is used to mimic MS pathophysiology.…”
Section: Current Research Investigating the Effects Of Aqp4 On Neuroimentioning
confidence: 94%
“…The presence of anti-AQP4 IgG remains a powerful and useful differential diagnostic tool in daily clinical practice [23], although it remains a question whether the presence of the autoantibody against AQP4 is the cause of the disease or a collateral consequence of some secondary pathological mechanism. Popescu et al [24] provided a plausible explanation for the absence of a secondary progressive clinical course in NMO; they showed that cognitive and cortical neuroimaging abnormalities previously reported in NMO cannot be attributed to cortical demyelination. They suggested that the lack of cortical demyelination is another characteristic that further distinguishes NMO from MS.…”
Section: Current Research Investigating the Effects Of Aqp4 On Neuroimentioning
confidence: 98%